Decomposition of n-hexane using a dielectric barrier discharge plasma. Issue 13 (7th June 2021) - Son, Youn-Suk; Kim, Junghwan; Choi, In-Young; Kim, Jo-Chun
ABSTRACT: In this study, we investigated the decomposition characteristics of n -hexane by a dielectric barrier discharge (DBD) plasma. In order to accomplish this, the factors influencing these decomposition characteristics such as background gases (air, N2, and He), residence time (1–10 s), initial n -hexane concentration (10–50 ppm), relative humidity (2.5%, 40%, and 70%), and power (50–80 W) were evaluated. As a result, the decomposition efficiency of n -hexane at N2 atmosphere was found to be lower than those at air and He atmosphere. The removal efficiency of n -hexane was increased when the residence time, relative humidity, and power increased, and when the initial concentration decreased. The concentrations of CO, CO2, and aerosol increased as the specific energy density increased. However, the O3 level increased up to a certain point, then decreased. Various hydrocarbons such as acetone, pentanal, nonanal, etc. were also detected as by-products and their decomposition and recombination pathways were suggested. GRAPHICAL ABSTRACT: UF0001